2021
DOI: 10.1080/09640568.2021.1920375
|View full text |Cite
|
Sign up to set email alerts
|

The political economy of industrial pollution control: environmental regulation in Swedish industry for five decades

Abstract: The paper analyzes the prerequisites for a regulatory-driven transition toward radically lower air and water pollution in industry. This is achieved in the empirical context of the Swedish mining and metals industry, and by investigating the environmental licensing processes during two regulatory systems. The paper derives an analytical framework that explores under what circumstances such licensing processes can result in radical emissions reductions without seriously jeopardizing the competitiveness of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Another emerging concept within the PPI is that of the biorefinery. A biorefinery entails a facility that integrates biomass conversion equipment and processes to produce power, fuels, and chemicals [58,401]. Biorefineries produce low-carbon commodities such as biofuels for transport and can also contribute to low-carbon energy supply, for instance, by feeding electricity and excess heat into the grid [16,39,154,402,403].…”
Section: Bioeconomy: An Emerging Business Model In the Ppimentioning
confidence: 99%
“…Another emerging concept within the PPI is that of the biorefinery. A biorefinery entails a facility that integrates biomass conversion equipment and processes to produce power, fuels, and chemicals [58,401]. Biorefineries produce low-carbon commodities such as biofuels for transport and can also contribute to low-carbon energy supply, for instance, by feeding electricity and excess heat into the grid [16,39,154,402,403].…”
Section: Bioeconomy: An Emerging Business Model In the Ppimentioning
confidence: 99%
“…Research by Söderholm et al (2022) into the environmental licensing of the Swedish mining and metals industry under two regulatory systems, suggests that the problem is not regulation per se but the good or bad design of regulation, noting that flexibility in both timeframes and forms of environmental action are fundamental.…”
Section: Public and Private Pressurementioning
confidence: 99%
“…Parallel to the development of technologies to reduce environmental pollution (Dechezleprêtre & Sato, 2017) or improvements in the social indicators of developing countries (Islam et al, 2021), researchers also found displacements of other innovations (Marin, 2014), reduced competitiveness, lower productivity (Oláh et al, 2020), and increasing indirect costs resulting in lower sales and employment (Rubashkina et al, 2015). Research by Söderholm et al (2022) into the environmental licensing of the Swedish mining and metals industry under two regulatory systems, suggests that the problem is not regulation per se but the good or bad design of regulation, noting that flexibility in both timeframes and forms of environmental action are fundamental.…”
Section: Corporate Environmental Behavior: Key Issuesmentioning
confidence: 99%
“…The problem of environmental pollution control is complicated, and the actual implementation effect is generally the result of a multiparty game in the process of implementing ER. 42 Owing to the different expected benefits faced by enterprises and the government and public, these three entities have conflicting goals, and their game relationships are complicated as well. When each participant puts forth a clear decision, it is easy to restrict and influence the others.…”
Section: Literature Reviewmentioning
confidence: 99%